Polysubstance use in treatment seekers who inject amphetamine: Drug use profiles, injecting practices and quality of life. (August 2017) - Kelly, Peter J.; Robinson, Laura D.; Baker, Amanda L.; Deane, Frank P.; McKetin, Rebecca; Hudson, Suzie; Keane, Carol
Abstract: Background: The injection of amphetamine is becoming increasingly common. However, there has been a lack of research examining people who inject amphetamine as the primary drug of use, limiting the potential to ensure services address the unique needs of this group. The current study used latent class analysis to identify classes of polydrug use among people who report injecting amphetamine during the past 12 months. It also examined differences between classes and drug use patterns, injecting practices, quality of life and psychological distress. Methods: Participants who were attending non-government specialist alcohol and other drug treatment across New South Wales, Australia and had identified amphetamine as their principle drug of concern and reported injecting amphetamine in the previous 12 months were included in the current study ( N = 827). Latent class analysis was performed to identify polydrug profiles of participants. Results: The large majority of people in the current study (85%) demonstrated low probability of heroin or other opiate use. Three distinct classes of polydrug use were identified: (1) Low-polydrug ( n = 491), (2) Opiates-polydrug ( n = 123), and (3) Alcohol-polydrug ( n = 213). There was a trend for the Low-polydrug class to demonstrate better functioning and safer injecting practices than the Opiates-polydrug and Alcohol-polydrug classes. Conclusion: The results suggest that the majority of people accessing treatment who inject amphetamine as their primary drug of choice have a low probability of heroin or other opiate use. It is important that future research consider whether traditional harm minimisation strategies are appropriate for people who primarily inject amphetamine. Highlights: Examines people who inject amphetamine as the primary drug of use Large sample of users accessing treatment services Identifies three distinct polydrug use classes using latent class analysis Polydrug use is linked with disadvantage and poorer functioning in this sample. Highlights a need for targeted interventions considering polydrug patterns